PAKETIN CANTING (Paket Kelas Catin Cegah Stunting) dalam Persiapan Biopsikososial Pranikah - Leila Nisya Ayuanda; Nur Intan Kusuma; Fitriyani (Ilin Institute, 2025)
Preconception Services, especially for prospective brides and grooms, aim to discover and change biomedical, psychological and social risks to women's health and pregnancy conditions with optimal early detection strategies. However, until now, services for prospective brides and grooms have only been limited to providing tetanus toxoid vaccination, which is currently not a prevention of the main problem. In fact, it is believed that the current problem of stunting can be prevented by optimally planning pregnancies and even marriages. So a strategy needs to be carried out in developing wedding planning through comprehensive pre-wedding classes. This community service aims to increase independence and empower health workers and prospective brides and grooms (catin) in optimal pre-wedding planning. The participants were 49 prospective brides and grooms. The method used is Participatory Action Research (PAR) by carrying out 3 activities carried out in stages. The activities carried out are screening of catin's physical and mental health, physical and mental preparation education, social and spiritual preparation education, and monitoring and evaluation. The results of community service, namely based on premarital biopsychosocial preparation before and after the catin class, showed an average increase of 52%. From the results of the community service program in the form of catin classes, in general there are differences between before and after the program.